The onus is not on us: Race and fan studies ten years after "African American acafandom and other strangers". - TWC Editor (Transformative Works & Cultures, 2024)
Rebecca Wanzo's landmark 2015 essay "African American Acafandom and Other Strangers" called for taking Black audiences, fandom, and critique seriously. In this roundtable interview, five Black scholars consider the impact of Wanzo's piece on their own research and centering Blackness in the field as a whole.